Soluble Microbial Products Removal Profile and Morphological Assessment of Submerged Ultrafiltration Membrane - Dizge, Nadir; Soydemir, Gulfem; Bayar, Secil; Karagunduz, Ahmet; Keskinler, Bulent (Journal of Membrane and Separation Technology, 2013)
Performance of ultrafiltration membranes were investigated with submerged membrane in terms of removal of soluble microbial products (SMP) (as proteins and carbohydrates) and fouling mechanisms. Cellulose (UC) and polyethersulphone (UP) membranes with different molecular weight cut off (MWCO) (5, 10, 30 kDa for UC and 5, 10, 20 kDa for UP) were tested in the bioreactor. The quality of permeate was compared in terms of SMP and COD. There was no significant difference in the total SMP removal effectives for both the UC and UP membranes with different MWCO characteristics. However, UP membranes were relatively more effective in removing soluble carbohydrates, while UC membranes were more effective in removing soluble proteins. The submerged membrane bioreactor achieved organic removal efficiencies ranging from 98.1±0.2% to 99.2±0.3% based on the soluble COD levels. Analysis of the membrane performance data by resistances-in-series model indicated that cake fouling was the dominant membrane fouling mechanisms. Increasing the MWCO was resulted in higher membrane flux but lower SMP removal. Morphological examination of the membranes by SEM and AFM showed significant accumulation of organisms on the membrane surface.